Environmental Variables of the Seti Gandaki River Basin Pokhara, Nepal - Pokharel, Kishor Kumar; Basnet, Khadga Bahadur; Majupuria, Trilok Chandra; Baniya, Chitra Bahadur (Journal of Institute of Science and Technology, 2018)
Present paper focuses on the spatio-temporal variations and correlations among the environmental variables of the Seti Gandaki River basin, Pokhara, Nepal. A total of five sites, three along the river and two in tributaries were selected for this study. Water sampling was done fortnightly for environmental variables following standard methods during July 2011 to June 2012. Mean and standard deviation of the environmental variables revealed that the depth (0.9 ± 0.3), pH (8 ± 0.4), total phosphates (PO4) (0.10 ± 0.03) and nitrates (NO3) (0.13 ± 0.04) were normally variable among the sites. But the discharge (40.00 ± 37.00), width (32.30 ± 13.00), turbidity (81.40 ± 51.00), transparency (29.10 ± 15.00), conductivity (166.00 ± 80.00), water temperature (18.00 ±4.00), dissolved oxygen (DO) (8.00 ± 2.00), free carbon dioxide (CO2) (7.00 ± 2.00) and total alkalinity (98.00 ± 22.00) varied among sites equally. Correlation coefficient between the sites and environmental variables revealed that sites were found significantly correlated with water conductivity (r2 = 0.6), DO (r2 = -0.52), and free CO2 (r2 = 0.6); depth of water with width (r2 = 0.94), discharge (r2 = 0.96), turbidity (r2 = 0.71), transparency (r2 = -0.62), water temperature (r2 = 0.60), pH (r2 = -0.52) and DO (r2 = -0.48); water temperature with pH (r2 = -0.54), DO (r2 = -0.79), free CO2 (r2 = 0.69), total alkalinity (r2 = -0.58), total PO4 (r2 = 0.54) and NO3 (r2 = 0.62), etc. The enhancement of turbidity, conductivity, free CO2, phosphates and nitrates, while, suppression of transparency, pH and DO at the urban site indicated the urban influence. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, page: 129-139